Characterization of an Amphiphilic Phosphonated Calixarene Carrier Loaded With Carboplatin and Paclitaxel: A Preliminary Study to Treat Colon Cancer in vitro and in vivo - Li, Meiying; Mao, Liujun; Chen, Meirong; Li, Mingxin; Wang, Kaixuan; Mo, Jingxin (Frontiers in Bioengineering and Biotechnology, 2019)
The inadequacy of available detection methods and a naturally aggressive progression have made colon cancer the third most common type of cancer, accounting for ~10% of all cancer cases. The heterogeneity and genomic instability of colon cancer tumors make current treatments unsatisfactory. This study evaluated a novel nanoscale delivery platform comprising phosphonated calixarenes (P4C6) co-loaded with paclitaxel (PTX) and carboplatin (CPT). The nanoparticles showed average hydrodynamic sizes of 84 ± 8 nm for empty P4C6 nanoparticle and 119 ± 13 nm for PTX-CPT-P4C6. The corresponding zeta potentials were −40.8 ± 8.8 and −35.4 ± 4.2 mV. The optimal CPT:PTX ratio was 5.22:1, and PTX-CPT-P4C6 with this ratio was more cytotoxic against HT-29 cells than against Caco-2 cells (IC50, 0.4 ± 0.02 vs. 2.1 ± 0.3 μM), and it induced higher apoptosis in HT-29 cells (56.6 ± 4.5 vs. 44.9 ± 3.44%). PTX-CPT-P4C6 inhibited the invasion and migration of HT-29 cells more strongly than the free drugs. It also inhibited the growth of HT-29 tumors in mice to the greatest extent of all formulations, with negligible side effects. This research demonstrates the potential of P4C6 to deliver two chemotherapeutic agents to colon cancer tumors to provide synergistic efficacy than single drug administration.